A Comparative Evaluation of Stress Distribution with Two Attachment Systems of Varying Heights in a Mandibular Implant‐Supported Overdenture: A Three‐Dimensional Finite Element Analysis. Issue 2 (6th September 2018) - Khurana, Nikita; Rodrigues, Shobha; Shenoy, Satish; Saldanha, Sharon; Pai, Umesh; Shetty, Thilak; N, Srikant; Mahesh, M; Hegde, Puneet
Abstract: Purpose: To analyze and compare the stress distribution in an implant‐retained overdenture complex using ball and Locator attachments of three heights by means of a 3D finite element analysis (FEA). Materials and Methods: Six finite element models comprising an edentulous mandible with two interforaminal bone‐level implants and ball attachments of heights 1 mm (A1), 3 mm (A3), and 5 mm (A5), and Locator attachments of heights 1 mm (B1), 3 mm (B3), and 5 mm (B5), were designed using ANSYS Workbench Software. Unilateral vertical (100 N) and oblique loads (100 N at 30° to the longitudinal axis of the implant in buccolingual direction) were applied. Average von Mises stress values were evaluated quantitatively and qualitatively. Results: Locator attachments showed lower stress values as compared to the ball attachments in all examined areas. The increase in the height of both resulted in increased stress values. Higher values were observed at the implant neck in all models, as compared to the body and the apex. The recorded stress was higher in the cortical bone as compared to the cancellous bone. Conclusions: Within the limitations of the study, Locator attachments demonstrated lesser and more homogenous stress distribution in the implant‐overdenture complex in comparison to ball attachments. The stresses generated within the tissues increase with an increase in collar height of the attachment system and therefore, attachments should be as short as possible for more favorable stress transmission.